Strategi Efektif Peningkatan Keterampilan Mengajar dalam Pembelajaran Microteaching - Maria Delarista Lau; Odillya Dessi L. Fatin Freitas; Gregolia edita Ikun; Donorius Agustinus Nahak; Ignasia Irmalinda Hale; Damian Puling; Augusta De Jesus Magalhaes (Journal Innovation In Education, 2025)
This study aims to identify and analyze effective strategies for improving student teaching skills through microteaching-based learning. Microteaching is a teaching training method that focuses on mastering basic teaching skills in a small-scale and controlled setting. Using a qualitative approach through participatory observation, in-depth interviews, and document analysis, the study found that strategies such as constructive and continuous feedback, the use of clear assessment rubrics, varied teaching simulations, and individualized mentoring significantly contribute to enhancing students’ pedagogical competence. The results indicate that the integration of these strategies creates a supportive and reflective learning environment, enabling students to identify weaknesses, improve their practices, and build confidence in teaching. The implication of this study highlights the importance of implementing structured and well-planned strategies within microteaching programs to produce professional and competent future teachers.